LIMITATIONS ON ASSETS. - Winakor, Arthur H. (The Accounting Review, 1936)
Although the title of this article would indicate that it is primarily concerned with assets, this is not the case. It is much more directly focused upon the liabilities including net worth, or the equities in those assets. These equities, through their priorities, their contractual restrictions upon the corporation and its assets, limit their use and disposal. They also indicate the participation in the assets as well as their earnings and losses. The true significance and relationships of the equities to the assets, as well as to one another, is usually obscured. Accountants particularly have failed to give due recognition to them. It is the purpose here to state these limit actions on assets, to point out their significance, and to show how serious has been the failure of accountants adequately to appraise them in their statements. Not infrequently certain classes of purchases are financed through short term or intermediate term notes. These notes may have special characteristics, which limit assets and their disposal. But these are quite similar to those found in certain bond indentures and preferred stock deeds. Hence, a few of the restrictions, common to all of these equities, as a class, may be discussed together. There are many provisions requiring the maintenance of given slims of working capital.